Islam and Terrorism: The Principle of Wasatiyyah Yusuf al-Qardhawi to Avert Incidents of Student Terrorism - Syahidin, Syahidin; Parhan, Muhamad; Islahuddin, Islahuddin (KARSA Journal of Social and Islamic Culture, 2023)
This research aims to explore and map the wasatiyyah concept offered by Yusuf Al-Qardhawi to counter radical movements and acts of terrorism that have become a serious concern for the Indonesian government. These issues and discourses continue to haunt the dynamics of students' religious life on campus. This research uses a qualitative approach with a literature review method, which is carried out by analyzing and discovering the concept of wasatiyyah. The results of the research found that the wasatiyyah concept can prevent thoughts, attitudes, and acts of terrorism for students who can strengthen and strengthen the foundations of thinking about Islam that rahmatan lil alamin by upholding the principles of tolerance, mutual respect, and respect for each other in creating harmony between people. Religious communities, thereby bridging divisions and confusion in the thinking of groups that view Islam as extreme, as well as minimizing ideologies that are contradictory to the values ​​of Islamic teachings, such as radicalism, terrorism, and acts of anarchism.